Finance and Development, March 1988. (Finance and Development; Finance and Development ;, 1988)
This paper examines the policy implications of structural changes in financial markets. Domestic financial markets have become less segmented, and the major financial centers more integrated. At the same time, the structural changes in financial markets have improved efficiency by lowering intermediation costs, increasing the ability to hedge financial risks associated with currency, interest rate, and price volatility and opening up access to new sources of savings. The widespread application of computer and telecommunications technology to financial markets has permitted markets to process a significantly larger volume of transactions.